2018
DOI: 10.1371/journal.ppat.1007073
|View full text |Cite
|
Sign up to set email alerts
|

An unappreciated role for neutrophil-DC hybrids in immunity to invasive fungal infections

Abstract: Neutrophils are classically defined as terminally differentiated, short-lived cells; however, neutrophils can be long-lived with phenotypic plasticity. During inflammation, a subset of neutrophils transdifferentiate into a population called neutrophil-DC hybrids (PMN-DCs) having properties of both neutrophils and dendritic cells. While these cells ubiquitously appear during inflammation, the role of PMN-DCs in disease remains poorly understood. We observed the differentiation of PMN-DCs in pre-clinical murine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
1
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 61 publications
1
42
1
3
Order By: Relevance
“…Moreover, retro-transmigrated neutrophils express CD54 and have been associated with secondary organ damage [14], as well as with effective bacterial phagocytosis during sepsis [95] (Figure 2). Overall, although the specific neutrophil subpopulations found in mouse models do not completely mirror their human counterparts (i.e., from cell-surface markers), important similarities are shared in terms of functionality (i.e., immunosuppressive activity, APC functions), as well as their influence on the outcomes of infections [84,[86][87][88]93,94]. As a result, mouse models are invaluable in that they can shed light on the importance of specific pathogen infections as possible sources of neutrophil heterogeneity; this information might in turn help in the development of tailored therapeutic strategies to improve host immune defense.…”
Section: Micementioning
confidence: 98%
See 2 more Smart Citations
“…Moreover, retro-transmigrated neutrophils express CD54 and have been associated with secondary organ damage [14], as well as with effective bacterial phagocytosis during sepsis [95] (Figure 2). Overall, although the specific neutrophil subpopulations found in mouse models do not completely mirror their human counterparts (i.e., from cell-surface markers), important similarities are shared in terms of functionality (i.e., immunosuppressive activity, APC functions), as well as their influence on the outcomes of infections [84,[86][87][88]93,94]. As a result, mouse models are invaluable in that they can shed light on the importance of specific pathogen infections as possible sources of neutrophil heterogeneity; this information might in turn help in the development of tailored therapeutic strategies to improve host immune defense.…”
Section: Micementioning
confidence: 98%
“…After encountering pathogens in the tissue, a subpopulation of CD11b high CD62L low C-X-C chemokine receptor type 2 (CXCR2) low neutrophils can migrate to the lymph node to promote adaptive immunity [91]. Populations of APC-like neutrophil-DC hybrids have also been identified in different mouse models of infection [92,93]. Moreover, after infection or sterile injury, CD54 + neutrophils can retro-transmigrate from the affected tissue to the bloodstream, exerting deleterious actions on secondary organs but also exhibiting an enhanced ability to fight pathogens [95].…”
Section: Mature Proinflammatory Neutrophilsmentioning
confidence: 99%
See 1 more Smart Citation
“…While the studies reported above describe APC‐like functions acquired by peripheral neutrophils, populations of so‐called ‘neutrophil–DC hybrids’, expressing markers of both neutrophils and DCs, have also been obtained from in vitro differentiation of murine and human neutrophil precursors, as well as isolated in vivo . These neutrophil–DC hybrids retain intrinsic functional abilities of neutrophils (including the capacity to capture exogenous material, extrude neutrophil extracellular traps and kill bacteria), but also exhibit several DC properties (including dendritic morphology, podosome formation and presentation of various forms of foreign protein antigens to naive CD4 + T cells) .…”
Section: Neutrophils and T Cellsmentioning
confidence: 99%
“…These neutrophil–DC hybrids retain intrinsic functional abilities of neutrophils (including the capacity to capture exogenous material, extrude neutrophil extracellular traps and kill bacteria), but also exhibit several DC properties (including dendritic morphology, podosome formation and presentation of various forms of foreign protein antigens to naive CD4 + T cells) . Given these unique features, a potential role of neutrophil–DC hybrids as potent effectors in anticancer immunity in humans, and antifungal defence in mice, has been recently proposed. In the former case, neutrophil–DC hybrids have been described as a population of tumour‐associated neutrophils (TANs) that infiltrate the tumour tissue in early‐stage lung cancer .…”
Section: Neutrophils and T Cellsmentioning
confidence: 99%